Differential protein expression between chondrogenic differentiated MSCs, undifferentiated MSCs and adult chondroctyes derived from oryctolagus cuniculus in vitro - Tay, L.X.; Lim, C.K.; Mansor, A.; Kamarul, Tunku (2014)
Objective: This preliminary study aims to determine the differentially expressed proteins from chondrogenic differentiated multipotent stromal cells (cMSCs) in comparison to undifferentiated multipotent stromal cells (MSCs) and adult chondrocytes (ACs). Methods: ACs and bone marrow-derived MSCs were harvested from New Zealand White rabbits (n = 3). ACs and cMSCs were embedded in alginate and were cultured using a defined chondrogenic medium containing transforming growth factor-beta 3 (TGF-beta 3). Chondrogenic expression was determined using type-II collagen, Safranin-O staining and glycosaminoglycan analyses. Two-dimensional gel electrophoresis (2-DE) was used to isolate proteins from MSCs, cMSCs and ACs before being identified using liquid chromatography-mass spectrometry (LC-MS). The differentially expressed proteins were then analyzed using image analysis software. Results: Both cMSCs and ACs were positively stained with type-II collagen and safranin-O. The expression of glycosaminoglycan in cMSCs was comparable to AC at which the highest level was observed at day-21 (p>0.05). Six protein spots were found to be most differentially expressed between MSCs, cMSCs and ACs. The protein spots cofilin-I (CFLI) and glycealde-hyde-3-phosphate dehydrogenase (GAPD) from cMSCs had expression levels similar to that of ACs whereas the others (ie. MYL6B, ALDOA, TAGLN2, EFI-alpha), did not match the expression level of ACs. Conclusion: Despite having similar phenotypic expressions to ACs, cMSCs expressed proteins which were not typically expected. This may explain the reason for the unexplained lack of improvement in cartilage repair outcomes reported in previous studies.